Diagnostic value of a novel automated simultaneous amplification and testing method in pulmonary tuberculosis and extrapulmonary tuberculosis - Ou, Xichao; Hu, Peilei; Bao, Xundi; Liu, Zhou; Teng, Chong; Guo, Jingwei; Xu, Dongfang; Li, Yue; Zhao, Bing; Xing, Ruida; Xia, Hui; Ma, Ling; et al. (Frontiers in Microbiology, 2025)
ObjectiveTo evaluate the clinical diagnostic ability of automated simultaneous amplification and testing (AutoSAT) method in suspected pulmonary tuberculosis (PTB) and extrapulmonary tuberculosis (EPTB) by comparing with Xpert MTB/RIF (Xpert) method against the composite reference standard.MethodPatients with suspected PTB or EPTB were enrolled consecutively from two provincial tuberculosis designated hospitals between August 2022 and December 2023. Clinical specimens were collected for routine clinical tests and AutoSAT.ResultsThe 297 patients including 90 PTB suspects and 207 EPTB suspects were eligible for final analysis. Among the 63 confirmed PTB, the sensitivity of Xpert was significantly higher than that of AutoSAT (30.16% vs. 28.57%, p < 0.001). Of the 18 bacteriologically confirmed PTB, equal sensitivity (94.44%) was observed between Xpert and AutoSAT. The higher specificity of AutoSAT than Xpert (100% vs. 96.30%, p = 0.803) was observed among PTB. The higher sensitivity of AutoSAT than Xpert was observed among confirmed EPTB (22.07% vs. 18.62%, p < 0.001) and bacteriologically confirmed EPTB patients (92.31% vs. 84.62%, p = 0.53), but the specificity (100%) was equal. And AutoSAT yielded higher sensitivity on pleural fluid (14.91% vs. 9.65%, p = 0.276). The same specificities (100%) were observed on different types of specimens.ConclusionAutoSAT is an accurate, sensitive and rapid method for the detection of Mycobacterium tuberculosis in both PTB and EPTB patients. AutoSAT is highly effective in bacteriologically confirmed PTB, and outperforms Xpert in paucibacillary EPTB patients, especially for pleural fluid specimen detection.